International Legal Acts of the Council of Europe Relating to the Criminal Law Regime of Juveniles - Ipokratova, Krasimira (Law Journal of New Bulgarian University, 2023)
The article examines the international legal acts of the Council of Europe, such as: “Guidelines for Child-Friendly Justice”, Resolution 2010 (2014) on Child-Friendly Justice: From Rhetoric to Reality, Recommendation SM/Rec (2008) 2011, on the European rules for juvenile and minor offenders subject to sanctions and measures.